Dampak Alih Fungsi Lahan Hutan Mangrove Bagi Keberlangsungan Sumber Daya Hayati Dan Lingkungan Desa Tanjung Luar - Asyri Febriana; Baiq Ishariaty Wika Utary (Universitas Muhammadiyah Surabaya, 2024)
Mangrove forests and coastal forests are green belts in coastal areas that have ecological and socio-economic functions. The main ecosystem in coastal areas is mangroves, which not only have economic value but also have great value for the environment. Tanjung Luar village, Keruak sub-district currently still really needs more attention and is still in the development stage, because most of the mangrove forests in the Tanjung Luar area have been converted into residential areas, shrimp ponds and salt ponds. This research aims to determine the impact of mangrove forest land conversion on the sustainability of biological resources and the environment of Tanjung Luar Village by reviewing environmental protection and management based on the environmental protection and management law. This research uses normative empirical research methods. The research results show that the impact of the conversion of mangrove forest land results in an imbalance in the marine ecosystem and has a direct impact on the community, especially people who earn a living as fishermen. Efforts that can be made to overcome this are by reforesting and reorganizing coastal spatial planning by involving the government, fisheries and marine services and the general public. Many cases of environmental pollution and damage are caused by human activities such as air pollution, water pollution, land pollution and forest damage which ultimately harm humans. Realizing the importance of living necessities and the high dependence on natural resources such as mangroves, a solution is needed to combine ecological, economic and socio-cultural aspects so that they are sustainable and thus support sustainable development programs. Several efforts that can be made to restore condition of mangrove forests are by involving the community to get involved directly. Such as conducting socialization on the importance of the negative impacts of environmental pollution, especially for the forest environment and the importance of mangroves for the sustainability of marine ecosystems and starting to replant mangrove forests which had previously been converted into residential areas by moving people who inhabit coastal areas with guaranteed compensation in the form of new settlements.